Assessing the vector competence of Italian Culex pipiens and Aedes albopictus mosquitoes for the re-emerging Oropouche virus - Elisa Mancuso; Francesco Severini; Luciano Toma; Giulia Marsili; Francesca Casale; Concetta Castilletti; Federico Giovanni Gobbi; Antonello Amendola; Christina Merakou; Martina Del Manso; Flavia Riccardo; Giulietta Venturi; et al. (Parasites & Vectors)
Abstract Background In 2024, Italy reported its first five cases of Oropouche fever in travelers returning from Cuba and Brazil. The Oropouche virus (OROV), an emerging Orthobunyavirus of the Peribunyaviridae family, is a zoonotic arbovirus responsible for febrile illnesses in humans, often misdiagnosed owing to its clinical similarity to those caused by dengue and Zika virus infections. Originally endemic to the Amazon region and first detected in Trinidad and Tobago in 1955, OROV has since spread throughout South and Central America. Recent outbreaks in Brazil and Cuba have been linked to the newly identified genotype V. Although Culicoides paraensis midges are recognized as the primary vector in the urban transmission cycle, their presence in Cuba was documented only after the outbreak. This late detection, coupled with a possibly low population density of this species, has raised concerns that other, more abundant arthropod species may have played a role in transmitting OROV to humans on the island. While some mosquito species have been implicated as potential OROV secondary vectors, their role remains uncertain. This study evaluates the vector competence of Italian populations of Aedes albopictus and Culex pipiens for the newly circulating OROV strain, which was introduced into the country by infected travelers. Methods Experimental infections were conducted under biosafety level 3 conditions, exposing adult female mosquitoes to an infectious blood meal containing OROV. Viral presence was assessed using a real-time RT-PCR in mosquito bodies, legs + wings, saliva, and the first gonotrophic progeny (F1). Results Results indicated that, while both species successfully ingested infectious virus particles, Cx. pipiens exhibited no signs of infection, dissemination, or transmission at any time point. In Ae. albopictus, viral RNA was detected in two body samples but not in saliva or disseminated tissues, confirming an absence of transmission capability. In addition, no evidence of transmission to F1 generation was detected in either species. These findings are consistent with previous research on American mosquito populations, indicating that barriers to OROV transmission likely occur at the midgut level. Conclusions Despite the apparent lack of vector competence in Italian Ae. albopictus and Cx. pipiens, the ongoing geographic expansion of OROV highlights the need for continued surveillance, particularly as the 2025 vector activity season approaches in Europe. The increasing circulation of the virus, along with its potential for adaptive evolution, highlights the importance of further research into the virus–vector interactions that could enable OROV to establish itself in new ecological niches. Graphical abstract